2021
DOI: 10.1186/s41118-021-00139-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating regional excess mortality during 2020 COVID-19 pandemic in selected Latin American countries

Abstract: In this paper, we measure the effect of the 2020 COVID-19 pandemic wave at the national and subnational levels in selected Latin American countries that were most affected: Brazil, Chile, Ecuador, Guatemala, Mexico, and Peru. We used publicly available monthly mortality data to measure the impacts of the pandemic using excess mortality for each country and its regions. We compare the mortality, at national and regional levels, in 2020 to the mortality levels of recent trends and provide estimates of the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 74 publications
1
62
0
11
Order By: Relevance
“…Selected studies focusing on regional excess mortality during 2020 in countries not included in the current study have also reported geographical discrepancies 23 , 28 . A study focusing in selected Latin America countries found that the subregions of Roriama, Lima, Puebla and Santa Elena were the subregions most affected in Brazil, Peru, Mexico and Ecuador with the percentage increase in the excess mortality varying from 50 to 160% during 2020 28 . These values are much higher compared to the maximum observed increase in excess mortality in our study which was 33% increase in males across all ages in Madrid.…”
Section: Discussionmentioning
confidence: 84%
“…Selected studies focusing on regional excess mortality during 2020 in countries not included in the current study have also reported geographical discrepancies 23 , 28 . A study focusing in selected Latin America countries found that the subregions of Roriama, Lima, Puebla and Santa Elena were the subregions most affected in Brazil, Peru, Mexico and Ecuador with the percentage increase in the excess mortality varying from 50 to 160% during 2020 28 . These values are much higher compared to the maximum observed increase in excess mortality in our study which was 33% increase in males across all ages in Madrid.…”
Section: Discussionmentioning
confidence: 84%
“…(2) in Russia relative to the rest of Europe (Islam et al 2021), and foremost, (3) in some Central and South American nations (Lima et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The final two papers in this Genus thematic series, Dorrington et al ( 2021 ) and Lima et al ( 2021 ), document technical challenges and practical solutions to analyzing excess mortality during the COVID-19 pandemic in countries where death registration is incomplete—namely Brazil, Chile, Ecuador, Guatemala, Mexico, Peru, and South Africa. Such analyses have informed public understanding of the COVID-19 pandemic and shaped policy responses (Agrawal et al, 2021 ; Clarke et al, 2021 ; Goldstein & Lee, 2020 ; Helleringer & Queiroz, 2021 ; Polyakova et al, 2020 ; Viglione, 2020 ).…”
Section: The Use Of Incomplete and Deficient Death Registration Data ...mentioning
confidence: 99%
“…Lima et al ( 2021 ) evaluate monthly death registration data in six Latin American countries during the COVID-19 pandemic to understand impact on life expectancy at birth. Similarly to Dorrington et al ( 2021 ), they contend with notable variability in underregistration of deaths, delayed registration issues, and variations in the place of occurrence and place of registration.…”
Section: The Use Of Incomplete and Deficient Death Registration Data ...mentioning
confidence: 99%